Hybrid fitting method for dynamic responses of mechanical systems - Zhang, Tangyun; Zhang, Bao; Su, Xiaoping; Zou, Liang (Frontiers in Mechanical Engineering, 2025)
For linear system, vibration response can be obtained by working load and vibration transfer function. However, for nonlinear systems, the vibration transfer function is variable, so the error of the existing methods is obvious. In order to improve the fitting precision of nonlinear system vibration response, a hybrid fitting method is proposed. That is, the vibration response is fitted by the vibration transfer function and the working load test. The influence of nonlinear parameters on the vibration transfer function is analyzed. A hybrid fitting method is used to identify the body acceleration on Class A, Class B and Class C pavement, and the analysis results are compared with the test results. The agreement between fitting results and test results is more than 90%. The results show that the hybrid fitting method proposed in this paper can significantly improve the fitting accuracy of nonlinear system vibration response.